2000
DOI: 10.1021/ma991272t
|View full text |Cite
|
Sign up to set email alerts
|

Micellar Copolymerization of Styrene with Poly(ethylene oxide) Macromonomer in Water:  Approach to Unimolecular Nanoparticles via Pseudo-Living Radical Polymerization

Abstract: Micellar copolymerizations of amphiphilic ω-methoxy-α-p-styrylalkyl poly(ethylene oxide) (PEO) macromonomers 1 (C1−PEO−C m −S-n, m = 1, 4, 7 and n = 18) with a limited amount of styrene solubilized therein have been investigated. The reactions were carried out with 4,4‘-azobis(4-cyanovaleric acid) (AVA) as a water-soluble initiator and 2,2‘-azobis(isobutyronitrile) (AIBN) as an oil-soluble initiator at 60 °C. Fractional time-evolution experiments revealed that the copolymerization rate of styrene is greatly en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
40
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 26 publications
3
40
0
Order By: Relevance
“…Ito et al observed unusually high polymerization rates, they explained by the organization of the polymerizable groups in hydrophobic domains, the micelle and they called it micellar organization polymerization. Kinetic studies by ESR [17] confirmed the very rapid polymerization due to high local concentration of radicals and (macro)monomers corresponding to enhanced rate of propagation and reduced termination. Micelle formation was confirmed unambiguously by surface tension and light scattering experiments.…”
Section: Peo Macromonomer Polymerization 321 Preliminary Remark αmentioning
confidence: 83%
See 1 more Smart Citation
“…Ito et al observed unusually high polymerization rates, they explained by the organization of the polymerizable groups in hydrophobic domains, the micelle and they called it micellar organization polymerization. Kinetic studies by ESR [17] confirmed the very rapid polymerization due to high local concentration of radicals and (macro)monomers corresponding to enhanced rate of propagation and reduced termination. Micelle formation was confirmed unambiguously by surface tension and light scattering experiments.…”
Section: Peo Macromonomer Polymerization 321 Preliminary Remark αmentioning
confidence: 83%
“…Special attention was given to the influence of the presence of the hydrophobic co-monomer on the final properties of the resulting hydrogels. The relevance of this approach has been demonstrated recently by the group of Ito [17] who performed micellar co-polymerization of monofunctional PEO macromonomers with styrene to design a new type of nanoparticular system. Results of the free radical copolymerization of bifunctional PEO macromonomers with styrene are presented in Tables 2 and 3. As expected, cross-linking occurs.…”
Section: Free Radical Copolymerization Of Peo Macromonomers With Styrmentioning
confidence: 99%
“…[10][11][12][13][14][15][16] PEG macromonomers possessing a hydrophobic spacer in between the PEG chain and the polymerizable double bond was prepared as a monomer with an appreciable surfactant ability for dispersion polymerization. Because most of the PEG macromonomers prepared so far possess no functional group at the distal chain end, the prepared latex lacks functionality on the surface.…”
Section: Resultsmentioning
confidence: 99%
“…23,24 An increase in the number of publications on them has been accelerated since well-defined block and graft copolymers came to be prepared more easily by living radical polymerization techniques than by living ionic polymerization. [25][26][27] Micelles for amphiphilic random copolymers have also been well-studied on the basis of the advantage of convenient procedure for preparing the random copolymers over block and graft copolymers. …”
mentioning
confidence: 99%
“…23,24 An increase in the number of publications on them has been accelerated since well-defined block and graft copolymers came to be prepared more easily by living radical polymerization techniques than by living ionic polymerization. [25][26][27] Micelles for amphiphilic random copolymers have also been well-studied on the basis of the advantage of convenient procedure for preparing the random copolymers over block and graft copolymers. [28][29][30][31][32] While many amphiphilic copolymers are utilized for preparing micelles, ''nonamphiphilic'' copolymers attract considerable attention in recent years because of the advantages in the molecular design.…”
mentioning
confidence: 99%